PENGUNDURAN DIRI SUKARELA SEBAGAI PENYELUNDUPAN HUKUM PEMUTUSAN HUBUNGAN KERJA SELAMA PANDEMI COVID-19 - Gde Wiryawan, I Wayan (Faculty of Law, Universitas 17 Agustus 1945 Surabaya, 2021)
Abstract The Covid-19 pandemic has implications for the weakening of the global economy. Many companies cannot operate or cannot operate optimally. In making efficiency with company expenses, the company reduces the number of employees, and some even close the business permanently. To reduce costs incurred by companies in the mechanism of termination of employment, the company uses a voluntary resignation statement. This condition is certainly detrimental to workers. This research will discuss firstly the protection of workers during the Covid-19 pandemic and second, the comparison of legal consequences of termination of employment with voluntary resignation. Protection of workers during the Covid-19 pandemic is based on a philosophical basis where the state has a legal obligation to create welfare for its people through the concept of a welfare state. Therefore, the state issued a series of policies to protect workers from termination of employment. One form of employment termination created by the company is by asking workers to sign a letter of voluntary resignation. In the event of termination of employment, the employer is obliged to pay severance pay and/or compensation for years of service and compensation for entitlements that should be received, whereas if the worker resigns voluntarily, the employer does not pay all the components of the right.Keywords: company; resignation; work terminationAbstrakPandemi Covid-19 berimplikasi pada pelemahan ekonomi global. Banyak perusahaan yang tidak dapat beroperasi atau tidak dapat beroperasi secara optimal. Dalam melakukan efesien terhadap pengeluaran perusahaan, maka perusahaan mengurangi jumlah karyawan, bahkan ada yang menutup usaha secara permanen. Untuk mengurangi biaya yang perlu dikeluarkan oleh perusahaan dalam mekanisme pemutusan hubungan kerja, maka perusahaan menggunakan surat pernyataan pengunduran diri secara sukarela. Kondisi ini tentu merugikan pekerja. Dalam penelitian ini akan dibahas mengenai pertama perlindungan tenaga kerja pada masa pandemi Covid-19 dan kedua, perbandingan akibat hukum pemutusan hubungan kerja dengan pengunduran diri sukarela. Perlindungan tenaga kerja pada masa pandemi Covid-19 didasarkan pada dasar filosofi dimana negara memiliki kewajiban hukum untuk menciptakan kesejahteraan bagi rakyatnya melalui konsep welfare state. Oleh sebab itu, negara mengeluarkan serangkaian kebijakan untuk melindungi tenaga kerja dari pemutusan hubungan kerja. Salah satu bentuk pemutusan tenaga kerja yang diciptakan oleh perusahaan adalah dengan meminta pekerja untuk menandatangangi surat pernyataan pengunduran diri secara sukarela. Dalam hal terjadi pemutusan hubungan kerja pengusaha diwajibkan membayar uang pesangon dan atau uang penghargaan masa kerja dan uang penggantian hak yang seharusnya diterima, sedangkan apabila pekerja mengundurkan diri secara sukarela maka pengusaha tidak membayarkan seluruh komponen hak tersebut.